Delivering an enabling environment and multiple benefits for land degradation neutrality: Stakeholder perceptions and progress. Issue 114 (December 2020) - Allen, Cameron; Metternicht, Graciela; Verburg, Peter; Akhtar-Schuster, Mariam; Inacio da Cunha, Marcelo; Sanchez Santivañez, Marioldy
Highlights: We identify 15 elements of an enabling environment for LDN. We survey LDN stakeholders to seek their views on progress and importance. High stakeholder expectations that achieving LDN could provide multiple benefits. National progress is widespread but gaps in awareness, buy-in and capacity remain. Greater efforts are needed to educate and raise awareness and profile of LDN. Abstract: Achieving land degradation neutrality (LDN) was adopted by countries in 2015 as one of the targets of the global Sustainable Development Goals (SDGs). As LDN is a relatively new concept there is an increasing need for evidence on the potential socio-economic and environmental benefits of LDN as well as how an enabling environment for implementing LDN measures can be developed. This paper summarises the results from a global survey of LDN stakeholders, and a review of national progress in target setting that was commissioned by the United Nations Convention to Combat Desertification (UNCCD) in 2018. The study presents the perceptions of relevant stakeholders on the key components of an enabling environment for achieving and maintaining LDN (institutional, financial, policy/regulatory, and science-policy) as well as expectations of multiple benefits from its implementation. We also highlight key challenges and gaps in progress to date that are emerging from ongoing national target setting programs to implement LDN. The study finds that progress in implementing LDN has been widespread across countries. However there remains a lack of awareness of LDN and its key concepts along with high-level political buy-in. This may be impeding the integration of LDN into national development planning and budgeting processes where progress was assessed as limited. National capacities for securing land tenure and governance arrangements and integrated land use planning were perceived as comparatively low, further hampering the implementation of LDN. Despite these gaps, most stakeholders (>90 %) who participated in the global survey expected LDN to deliver a broad range of multiple benefits for human wellbeing, livelihoods and the natural environment. We argue that greater efforts are needed to raise awareness of LDN, educate core stakeholders in its concepts, enablers and benefits, raise its political profile, and provide evidence on national measures that will support implementation of LDN.